2003
DOI: 10.1017/s0263034602211027
|View full text |Cite
|
Sign up to set email alerts
|

Stopping power of dense helium plasma for fast heavy ions

Abstract: The interaction process between fast heavy ions and dense plasma was experimentally investigated. We injected 4.3-MeV0u or 6.0-MeV0u iron ions into a z-pinch-discharge helium plasma and measured the energy loss of the ions by the time of flight method. The energy loss of 4.3-MeV0u ions fairly agreed with theoretical prediction when the electron density of the target was on the order of 10 18 cm Ϫ3 . With increasing electron density beyond 10 19 cm Ϫ3 , the difference between the experiment and the theory becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…From earlier experiments with fully ionized hydrogen discharge and pinch plasmas it is well known, that ionized matter has an increased stopping power for heavy ions~Hoffmann et al, 1990;Jacoby et al, 1995;Roth et al, 2000;Hasegawa et al, 2003!, and that the charge state of heavy ion beams passing through plasma is considerably altered~Dietrich et al, 1992!. In order to achieve plasma parameters which extend far beyond those of discharge and pinch plasmas a laser Nd: glass laser system with total laser beam pulse energy well above 100 J was installed.…”
Section: Introductionmentioning
confidence: 99%
“…From earlier experiments with fully ionized hydrogen discharge and pinch plasmas it is well known, that ionized matter has an increased stopping power for heavy ions~Hoffmann et al, 1990;Jacoby et al, 1995;Roth et al, 2000;Hasegawa et al, 2003!, and that the charge state of heavy ion beams passing through plasma is considerably altered~Dietrich et al, 1992!. In order to achieve plasma parameters which extend far beyond those of discharge and pinch plasmas a laser Nd: glass laser system with total laser beam pulse energy well above 100 J was installed.…”
Section: Introductionmentioning
confidence: 99%
“…The initial pressure of hydrogen gas in the shock tube was varied from 0.13 to 6.7 kPa. Then we calculated the energy loss of 10-20 keV/u Pb ions in the hydrogen plasmas by using an ion stopping calculation code including charge exchange processes of projectiles [7]. The initial projectile charge was varied from 2 to 10.…”
Section: Estimation Of G Values Under Various Conditionsmentioning
confidence: 99%
“…This so-called ''plasma effect'' has been examined experimentally by many research groups for the last two decades [1][2][3][4][5][6][7]. In these studies high-current discharges or high-power lasers produced ''classical'' plasma targets.…”
Section: Introductionmentioning
confidence: 99%
“…In the related experiments, time-of-flight (TOF) is one of the most powerful diagnostics for the purpose in the framework of particle diagnostics Oguri et al, 2000;Hasegawa et al, 2003). In the category of X-ray diagnostics, which is also one of the promising tools for the above purpose, Goel et al (1998) demonstrated some numerical calculations of Kα spectra from low-Z target material heated by a proton beam.…”
Section: Introductionmentioning
confidence: 99%